Composition for geopolymer, geopolymer and preparation method of geopolymer

By rationally designing the composite of fiber and inorganic polymers in geological polymers, and using aramid fibers and graphitized carbon fibers of a specific proportion, the problem of degradation of the mechanical properties of geological polymers in high temperature environments is solved, and its excellent mechanical properties and low loss rate in high temperature environments are achieved.

CN119912210AActive Publication Date: 2025-05-02SHANGHAI GEOPOLY NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510399879.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

Geopolymers have significantly reduced mechanical properties and structural stability under extremely high temperature conditions, especially in high temperature environments above 600°C, which limits their application in high-temperature engineering.

Method used

By rationally designing the composite of fiber and inorganic polymer in geological polymer, using aramid fiber and graphitized carbon fiber in a specific proportion, and combining gelled materials containing alkali exciters and blends, the prepared geological polymer has excellent high temperature resistance.

Benefits of technology

Geopolymers exhibit excellent mechanical properties and low mass and volume loss rates in high temperature environments, solving the problem of performance degradation in high temperature environments and providing a better engineering application solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of building materials, and discloses a composition for a geopolymer, the geopolymer and a preparation method of the geopolymer. The composition contains a cementing material and a fiber material, the cementing material comprises an alkali activator and an admixture; the admixture contains metakaolin and fly ash; the mass ratio of the binding material to the fiber material is 100: (0.5-1.5); the fiber material contains aramid fiber and graphitized carbon fiber in a mass ratio of 1: (0.3-3). The geopolymer provided by the invention has excellent high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a geopolymer composition, a geopolymer and a preparation method thereof. Background Art

[0002] Geopolymer, as an environmentally friendly building material, has attracted extensive attention due to its excellent high temperature resistance, acid and alkali resistance, and corrosion resistance. Geopolymer is mainly synthesized by the reaction of aluminum silicon sources (such as metakaolin MK and fly ash FA) in a strong alkaline environment, and has chemical stability and mechanical properties that traditional cement cannot match. However, under extreme high temperature conditions, especially in high temperature environments above 600°C, the mechanical properties and structural stability of geopolymer will significantly decrease, limiting its application in high temperature engineering.

[0003] In recent years, the incorporation of fibers (inorganic or organic fibers) has become an effective means to improve the high-temperature performance of geopolymers. Fibers can not only enhance the toughness and crack resistance of the matrix, but also effectively inhibit the propagation of cracks at high temperatures, thereby improving the overall thermal stability of the material.

[0004] Although fibers have certain advantages in improving the high temperature resistance of geopolymers, the synergistic effect of different types of fibers has not been fully explored. How to reasonably design the composite of fibers and inorganic polymers to exert their synergistic effect and improve the comprehensive performance of geopolymers has become a current research hotspot.

[0005] CN110981295A discloses a geopolymer-based self-induction anchoring mortar, comprising the following components: 100-120 parts of river sand, 30-40 parts of metakaolin, 10-20 parts of fly ash, 60-70 parts of alkali activator, 15 parts of expansion agent, 0.5-1 parts of carbon fiber, and 0.2-0.5 parts of carbon nanotubes. However, this solution has the problem that carbon fiber and carbon nanotubes are prone to agglomeration in the viscous geopolymer matrix and the cost is too high. In addition, the composite geopolymer synthesized in this solution does not show good high temperature resistance.

[0006] CN110255996A discloses a fly ash geopolymer concrete, which is prepared by using fly ash and metakaolin as the base material, sodium hydroxide, potassium hydroxide, potassium silicate or a combination of one or more thereof and water glass as the alkaline activator, adding modified ceramic microsphere particles, polymer fiber, coarse aggregate, fine aggregate, and water; the modified ceramic microsphere particles are prepared by coating a functional coating containing an anticorrosion and rust inhibitor on the surface of ordinary ceramic microspheres, and the raw materials for preparation thereof include: 100-500 parts of ceramic microspheres, 20-60 parts of silica sol, 20-40 parts of anticorrosion and rust inhibitor, and 30-50 parts of acrylate emulsion and / or styrene-acrylic emulsion in total. However, the scheme has the problems of complex preparation process, high cost, and the styrene-acrylic emulsion used contains volatile organic matter (TVOC>50μg / m³), which violates the green building material certification standards. Summary of the invention

[0007] The purpose of the invention is to overcome the technical problem that geopolymer has poor high temperature resistance.

[0008] In order to achieve the above object, the first aspect of the present invention provides a geopolymer composition, which contains a gelling material and a fiber material; the gelling material includes an alkali activator and an admixture; the admixture contains metakaolin and fly ash; The mass ratio of the gelling material to the fiber material is 100:0.5-1.5; The fiber material contains aramid fiber and graphitized carbon fiber in a mass ratio of 1:0.3-3; The aramid fiber has a tensile modulus of 100-150 GPa at 25° C. and a tensile strength of 3-6 GPa at 25° C.

[0009] The second aspect of the present invention provides a method for preparing a geopolymer, which is carried out using the geopolymer composition of the first aspect. The method comprises: mixing the components in the geopolymer composition with water to obtain the geopolymer.

[0010] The third aspect of the present invention provides a geopolymer prepared by the method of the second aspect.

[0011] The present invention has at least the following advantages: (1) The geopolymer of the present invention has excellent high temperature resistance and stability, and exhibits excellent mechanical properties and low mass loss rate under high temperature environment.

[0012] (2) The preparation process of the present invention is simple and environmentally friendly. DETAILED DESCRIPTION

[0013] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0014] It should be noted that, in various aspects of the present invention, for the same components or terms in various aspects, the present invention is described only once in one aspect without repeated description, which should not be understood by those skilled in the art as a limitation of the present invention.

[0015] As mentioned above, the first aspect of the present invention provides a geopolymer composition, which contains a gelling material and a fiber material; the gelling material includes an alkali activator and an admixture; the admixture contains metakaolin and fly ash; The mass ratio of the gelling material to the fiber material is 100:0.5-1.5; The fiber material contains aramid fiber and graphitized carbon fiber in a mass ratio of 1:0.3-3; The aramid fiber has a tensile modulus of 100-150 GPa at 25° C. and a tensile strength of 3-6 GPa at 25° C.

[0016] In the technical solution of the present invention, in aqueous solution, aramid fiber and graphitized carbon fiber are used as reinforcing fibers in a specific proportion, and a gelling material containing an alkali activator and an admixture is used. The prepared geopolymer exhibits excellent mechanical properties and low mass and volume loss rates under high temperature environments, providing an excellent solution for engineering applications under high temperature environments.

[0017] Preferably, the modulus of the base activator is 0.8-1.2.

[0018] It should be noted that the modulus of the alkaline activator in the present invention refers to the molar ratio of silicon dioxide (SiO2) to total sodium oxide (Na2O) in the alkaline activator system, wherein silicon dioxide and sodium oxide are obtained by chemically converting the actual components of the raw materials.

[0019] Preferably, the mass ratio of the alkali activator to the admixture is 1:3-5.

[0020] Preferably, the mass ratio of the metakaolin to the fly ash is 1:0.1-1. The inventors of the present invention have found that under this preferred condition, the overall performance of the material can be significantly improved. Specifically, this ratio can effectively enhance the mechanical strength of the material, making it have better compressive strength and flexural strength, thereby improving its durability and stability. At the same time, the appropriate mass ratio also optimizes the fluidity of the mixture and reduces the difficulty of operation during the production process.

[0021] Preferably, the fly ash in the present invention is primary and / or secondary fly ash specified in the GB / T 1596-2017 "Fly ash used in cement and concrete" standard.

[0022] According to a preferred embodiment, the graphitized carbon fiber is a product prepared by the following steps: The carbon fiber is graphitized to obtain the graphitized carbon fiber; the graphitization conditions include: a temperature of 1200-1500°C and a time of 24-36h. The inventors of the present invention have found that by preparing the graphitized carbon fiber material at 1200-1500°C, it is beneficial to significantly improve the thermal stability and mechanical properties of the carbon fiber. Graphitization treatment within this high temperature range helps the carbon atoms to be arranged more orderly and form a more compact graphite layer structure, thereby increasing the density and rigidity of the material and enhancing its high temperature resistance.

[0023] It should be noted that the present invention has no restrictions on the source of the carbon fiber, which may include carbon fiber from industrial production waste. The geopolymer prepared by graphitization treatment under specific conditions and in combination with the remaining components of the present invention has excellent high temperature resistance. At the same time, the use of discarded carbon fiber can effectively utilize waste resources, which has the advantages of environmental protection and low cost.

[0024] More preferably, the length of the graphitized carbon fiber is 4-6 mm.

[0025] Preferably, the graphitized carbon fiber has a tensile modulus of 200-300 GPa at 25°C, a tensile strength of 3-6 GPa at 25°C, and a density of 1-3 g / cm³.

[0026] More preferably, the aramid fiber has a density of 1-3 g / cm³ and a length of 4-6 mm.

[0027] Preferably, the alkaline activator is a combination of water glass and sodium hydroxide.

[0028] As mentioned above, the second aspect of the present invention provides a method for preparing a geopolymer, which is carried out using the geopolymer composition of the first aspect, and comprises: mixing the components in the geopolymer composition with water to obtain a geopolymer.

[0029] Preferably, the amount of water is controlled to satisfy a water-to-binder ratio of 0.35-0.45.

[0030] It should be noted that the water-gel ratio in the present invention refers to the ratio of the total mass of water in the material system to the total mass of the active gelling components, wherein the active gelling components include two types of substances that participate in the alkali excitation reaction: the first type is siliceous-aluminous materials with volcanic ash activity, such as metakaolin with a chemical structure of Al2O3·2SiO2, fly ash with a component expression of mSiO2·nAl2O3, etc.; the second type is the functional components in the alkaline excitation system, specifically the functional components that can dissociate in an alkaline environment to generate silicate ions (SiO3 2- )'s active silicon source (such as the SiO2 component in sodium silicate Na2O·nSiO2) and alkaline oxides calculated as equivalent oxides (such as the Na2O component in sodium silicate, and other alkali metal oxides K2O, CaO, etc.). The mass of the alkaline oxides needs to be converted to chemical equivalents based on the actual components of the raw materials.

[0031] Preferably, the mixing treatment conditions include: stirring speed of 100-1200 rpm, stirring time of 2.5-6 h, and reaction temperature of 20-50°C.

[0032] According to a preferred embodiment, the mixing process comprises: (1) first mixing a solution 1 containing the alkali activator and water with the fiber material to obtain a solution 2; (2) The solution 2 is mixed with the admixture for a second time to obtain a geopolymer.

[0033] In the present invention, by controlling the order of adding different raw materials, the reaction process is made more controllable and the interaction between the raw materials is more uniform, ensuring that the prepared geopolymer exhibits better mechanical properties and lower mass and volume loss rates under high temperature environment.

[0034] Preferably, the temperature of the first mixing and the second mixing is independently selected from 20-50° C., the stirring speed is independently selected from 100-1200 rpm, and the total mixing time is 2.5-6 h.

[0035] According to a preferred embodiment, the method further comprises: subjecting the product obtained by the mixing process to injection molding and curing treatment in sequence to obtain the geopolymer.

[0036] Preferably, the curing treatment conditions include: temperature of 60-90°C, time of 48-60h, and relative humidity of 85-95%.

[0037] The present invention has no particular limitation on the operation of the injection molding, and those skilled in the art can make their own selections based on technical means known in the art. The present invention exemplifies a preferred specific implementation method in the following text, which will not be described in detail here, and those skilled in the art should not interpret it as a limitation on the present invention.

[0038] As mentioned above, the third aspect of the present invention provides a geopolymer prepared by the method described in the second aspect.

[0039] In the following examples, unless otherwise specified, the raw materials are all common commercially available products.

[0040] Aramid fiber 1: tensile modulus at 25°C is 150 GPa, tensile strength at 25°C is 6 GPa, density is 2.8 g / cm³, length is 5 mm, purchased from Hubei Jiateng Textile Co., Ltd.

[0041] Aramid fiber 2: tensile modulus at 25°C is 150 GPa, tensile strength at 25°C is 1.5 GPa, density is 1.3 g / cm³, length is 5 mm, purchased from Hubei Jiateng Textile Co., Ltd.

[0042] Aramid fiber 3: tensile modulus at 25°C is 100 GPa, tensile strength at 25°C is 4.5 GPa, density is 1.25 g / cm³, length is 5 mm, purchased from DuPont.

[0043] Carbon fiber: Model STT49S, purchased from Hubei Jiateng Textile Co., Ltd.

[0044] Water glass: modulus 3.3, CAS number: 1344-09-8, purchased from Jiashan Yourui Refractory Material Co., Ltd.

[0045] The test method of tensile modulus in the present invention refers to GB / T3362-2017.

[0046] The test method for tensile strength in the present invention refers to GB / T3362-2017.

[0047] The density test method of the present invention is based on GB / T30019-2013.

[0048] Preparation Example 1 The 5 mm carbon fiber was heated to 1200° C. at 10° C. / min and maintained at the temperature for 24 hours to obtain graphitized carbon fiber 1; The graphitized carbon fiber 1 has a tensile modulus of 220 GPa at 25°C, a tensile strength of 4.9 GPa at 25°C, and a density of 1.8 g / cm³.

[0049] Preparation Example 2 The 2 mm carbon fiber was heated to 1200° C. at 10° C. / min and maintained at the temperature for 24 hours to obtain graphitized carbon fiber 2; The graphitized carbon fiber 2 has a tensile modulus of 200 GPa at 25°C, a tensile strength of 2.8 GPa at 25°C, and a density of 1.4 g / cm³.

[0050] Example 1 (1) 54 g of sodium hydroxide and 212.7 g of water glass (the modulus of the alkali activator is 1) are stirred and mixed in an aqueous solution to obtain a solution 1; and the solution 1 is allowed to stand for 24 hours; the stirring and mixing conditions are: a stirring speed of 1200 rpm, a time of 0.5 h, and a temperature of 20°C; (2) 5 g of graphitized carbon fiber 1 and 5 g of aramid fiber 1 were first mixed with solution 1 to obtain solution 2; the conditions of the first mixing were: stirring speed of 1200 rpm, time of 2 h, and temperature of 45° C.; (3) 750 g of metakaolin and 250 g of fly ash were stirred at 150 rpm for 2 min to obtain an admixture; the admixture and solution 2 were mixed for a second time to obtain a geopolymer slurry; the second mixing operation was: first stirring at 150 rpm for 2 min, then stirring at 750 rpm for 2 min, and the temperature was 20°C; The water-binder ratio in the geopolymer slurry is 0.4; the mass ratio of the alkali activator (sodium hydroxide and water glass) to the admixture (metakaolin and fly ash) is 1:3.7; the mass ratio of metakaolin and fly ash is 1:0.33; the mass ratio of the cementitious material (alkali activator, metakaolin and fly ash) to the fiber material (graphitized carbon fiber and aramid fiber) is 100:0.79; (4) The geopolymer slurry was quickly poured into a triple steel mold with a size of 4 cm × 4 cm × 16 cm and sealed and molded. The mold was demolded after 24 hours. The demolded product was then placed in an 80°C steam curing box for 48 hours (relative humidity of 90%) and then transferred to a standard curing room (relative humidity of 90%) for 4 days to obtain a geopolymer.

[0051] Example 2 The same process as in Example 1 is adopted, except that: in this example, the amount of graphitized carbon fiber 1 is 6 g, the amount of aramid fiber 1 is 4 g, and the rest is the same as in Example 1 to obtain a geopolymer.

[0052] Example 3 The same process as in Example 1 is adopted, except that the amount of graphitized carbon fiber 1 used in this example is 6.7 g, the amount of aramid fiber 1 used in this example is 3.3 g, and the rest is the same as in Example 1 to obtain a geopolymer.

[0053] Example 4 The same process as in Example 1 is adopted, except that: in this example, the amount of graphitized carbon fiber 1 is 4 g, the amount of aramid fiber 1 is 6 g, and the rest is the same as in Example 1 to obtain a geopolymer.

[0054] Example 5 The same process as in Example 1 is adopted, except that: in this example, the amount of graphitized carbon fiber 1 is 3.3 g, the amount of aramid fiber 1 is 6.7 g, and the rest is the same as in Example 1 to obtain a geopolymer.

[0055] Example 6 The same process as in Example 1 is adopted, except that the amount of kaolin and fly ash is adjusted to 1:1.5 while ensuring that the total amount of the admixture remains unchanged, and the rest is the same as in Example 1 to obtain a geopolymer.

[0056] Example 7 The same process as in Example 1 is adopted, except that the graphitized carbon fiber 1 is replaced by the graphitized carbon fiber 2 of the same mass, and the rest is the same as in Example 1, to obtain a geopolymer.

[0057] Example 8 The same process as in Example 1 was adopted, except that: in this example, while keeping the amount of 266.7 g of the alkali activator unchanged, the amounts of sodium hydroxide and water glass were adjusted so that the modulus of the alkali activator was 1.5, and the rest was the same as in Example 1 to obtain a geopolymer.

[0058] Example 9 (1) In an aqueous solution, 54 g of sodium hydroxide, 212.7 g of water glass (the modulus of the alkali activator is 1), 5 g of graphitized carbon fiber 1, 5 g of aramid fiber 1, 750 g of metakaolin and 250 g of fly ash are mixed to obtain a geopolymer slurry; the mixing conditions are: stirring speed 750 rpm, time 2 h, temperature 20 ° C; The water-binder ratio in the geopolymer slurry is 0.4; the mass ratio of the alkali activator (sodium hydroxide and water glass) to the admixture (metakaolin and fly ash) is 1:3.7; the mass ratio of metakaolin and fly ash is 1:0.33; the mass ratio of the cementitious material (alkali activator, metakaolin and fly ash) to the fiber material (graphitized carbon fiber and aramid fiber) is 100:0.79; (2) The geopolymer slurry was quickly poured into a triple steel mold with a size of 4 cm × 4 cm × 16 cm and sealed and molded. The mold was demolded after 24 hours. The demolded product was then placed in an 80°C steam curing box for 48 hours (relative humidity of 90%) and then transferred to a standard curing room (relative humidity of 90%) for 4 days to obtain the geopolymer.

[0059] Example 10 The same process as in Example 1 is adopted, except that the aramid fiber 1 is replaced by the aramid fiber 3 of the same mass, and the rest is the same as in Example 1, to obtain a geopolymer.

[0060] Comparative Example 1 This comparative example adopts the same process as Example 1, except that: in this comparative example, graphitized carbon fiber 1 and aramid fiber 1 are not added, the solution 1 obtained in step (1) is directly mixed with the admixture for a second time, and the rest is the same as Example 1 to obtain a geopolymer.

[0061] Comparative Example 2 This comparative example adopts the same process as Example 1, except that: in this comparative example, graphitized carbon fiber 1 is not added, and the rest is the same as Example 1 to obtain a geopolymer.

[0062] Comparative Example 3 This comparative example adopts the same process as Example 1, except that: in this comparative example, no graphitized carbon fiber 1 is added, and the amount of aramid fiber 1 is adjusted to 7.5 g, and the rest is the same as Example 1 to obtain a geopolymer.

[0063] Comparative Example 4 This comparative example adopts the same process as Example 1, except that: in this comparative example, no graphitized carbon fiber 1 is added, and the amount of aramid fiber 1 is adjusted to 10 g, and the rest is the same as Example 1 to obtain a geopolymer.

[0064] Comparative Example 5 This comparative example adopts the same process as Example 1, except that: the aramid fiber 1 is not added in this comparative example, and the rest is the same as Example 1 to obtain a geopolymer.

[0065] Comparative Example 6 This comparative example adopts the same process as Example 1, except that: in this comparative example, aramid fiber 1 is not added, and the amount of graphitized carbon fiber 1 is adjusted to 7.5 g, and the rest is the same as Example 1 to obtain a geopolymer.

[0066] Comparative Example 7 This comparative example adopts the same process as Example 1, except that: in this comparative example, aramid fiber 1 is not added, and the amount of graphitized carbon fiber 1 is adjusted to 10 g, and the rest is the same as Example 1 to obtain a geopolymer.

[0067] Comparative Example 8 This comparative example adopts the same process as Example 1, except that the aramid fiber 1 is replaced by the aramid fiber 2 of the same mass, and the rest is the same as Example 1 to obtain a geopolymer.

[0068] Comparative Example 9 The same process as in Example 1 was adopted, except that in this comparative example, the amount of metakaolin was adjusted to 1617 g, so that the mass ratio of the alkali activator to the admixture was 1:7, and the mass ratio of the metakaolin to the fly ash was 1:0.15. The rest was the same as in Example 1, and a geopolymer was obtained.

[0069] Test Case After the geopolymers prepared in the examples and comparative examples were calcined at 200°C, 400°C, 600°C and 800°C for 3h, their compressive strength and flexural strength were measured and the retention rates of the compressive strength and flexural strength were calculated: Flexural strength retention rate = flexural strength after calcination / flexural strength without calcination; Compressive strength retention rate = compressive strength after calcination / compressive strength without calcination.

[0070] The test methods for compressive strength and flexural strength refer to GB / T 17671-1999, and the specific parameters are shown in Tables 1 to 3.

[0071] Table 1

[0072] Table 2

[0073] Table 3

[0074] It can be seen from the data in Tables 1 to 3 that, compared with Example 1, the geopolymer prepared in Example 6 of the present invention, after calcination at 200°C, 400°C, 600°C and 800°C, has a certain degree of reduction in flexural strength retention, but a relatively good compressive strength retention and mass loss rate; that is, by adjusting the amount of metakaolin and fly ash in a specific ratio, it is helpful to further improve the mechanical properties of the geopolymer.

[0075] Compared with Example 1, the geopolymer prepared by Example 7 in the present invention still has good compression retention and flexural retention after calcination, but after calcination at 600° C. for 3 h, its mass loss rate reaches 30.43%; that is, the technical solution of the present invention using a specific type of graphitized carbon fiber helps to further reduce the mass loss of geopolymers in high temperature environments.

[0076] Compared with Example 1, the geopolymer prepared in Example 8 in the present invention has a mass loss rate of 30.07% after calcination at 800°C for 3h, but its compression retention rate and flexural retention rate in a high temperature environment are still good; that is, by regulating the modulus of the alkali activator, it is helpful to further reduce the mass loss of the geopolymer in a high temperature environment.

[0077] Compared with Example 1, the geopolymer prepared in Example 9 of the present invention has a slightly reduced flexural strength retention rate and compressive strength retention rate after calcination at 800°C for 3h, and its mass loss rate reaches 31.18%; that is, compared with the overall mixing treatment method, the step-by-step treatment helps the geopolymer to exhibit better mechanical properties and lower mass loss rate under high temperature environment.

[0078] The technical effects of the geopolymers prepared in Comparative Examples 1 to 9 of the present invention are significantly worse than those of the embodiments of the present invention. In order to ensure the practicability of the products, the geopolymers prepared in the embodiments of the present invention are required to have a mass loss rate of no more than 21%, a flexural strength retention rate of no less than 80%, and a compressive strength retention rate of no less than 90% after calcination at 200°C for 2h. If these requirements are not met, it means that the prepared geopolymers have obvious thermal stability defects. In practical engineering applications, the structural performance is easily deteriorated due to the insufficient temperature resistance of the materials at the initial stage of heating. However, it can be seen from the technical effects of Comparative Examples 1 to 9 that their performance obviously does not meet the requirements.

[0079] It can be seen from the above content that the geopolymer of the present invention obviously has better high temperature resistance.

[0080] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A geopolymer composition, characterized in that: The composition contains a cementitious material and a fiber material; the cementitious material includes an alkali activator and an admixture; the admixture contains metakaolin and fly ash; The mass ratio of the gelling material to the fiber material is 100:0.5-1.5; The fiber material contains aramid fiber and graphitized carbon fiber in a mass ratio of 1:0.3-3; The aramid fiber has a tensile modulus of 100-150 GPa at 25° C. and a tensile strength of 3-6 GPa at 25° C.

2. The composition according to claim 1, characterized in that The modulus of the base activator is 0.8-1.

2.

3. The composition according to claim 1 or 2, characterized in that The mass ratio of the alkali activator to the admixture is 1:3-5; And / or, the mass ratio of the metakaolin to the fly ash is 1:0.1-1.

4. The composition according to claim 1 or 2, characterized in that The graphitized carbon fiber is a product prepared by the following steps: The carbon fiber is graphitized to obtain the graphitized carbon fiber; the graphitization conditions include: a temperature of 1200-1500° C. and a time of 24-36 hours; And / or, the length of the graphitized carbon fiber is 4-6 mm.

5. The composition according to claim 1 or 2, characterized in that The graphitized carbon fiber has a tensile modulus of 200-300 GPa at 25°C, a tensile strength of 3-6 GPa at 25°C, and a density of 1-3 g / cm³; And / or, the aramid fiber has a density of 1-3 g / cm³ and a length of 4-6 mm; And / or, the alkaline activator is a combination of water glass and sodium hydroxide.

6. A method for preparing a geopolymer, characterized in that: The method is carried out using the geopolymer composition described in any one of claims 1 to 5, and comprises: mixing the components in the geopolymer composition with water to obtain a geopolymer.

7. The method according to claim 6, characterized in that The amount of water is controlled to meet the water-to-binder ratio of 0.35-0.

45.

8. The method according to claim 6 or 7, characterized in that: The mixing process includes: (1) first mixing a solution 1 containing the alkali activator and water with the fiber material to obtain a solution 2; (2) The solution 2 is mixed with the admixture for a second time to obtain the geopolymer.

9. The method according to claim 6 or 7, characterized in that: The method further comprises: sequentially subjecting the product obtained by the mixing process to injection molding and curing to obtain the geopolymer.

10. Geopolymer prepared by the method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • High-strength refractory concrete

    CN102976779A

  • High-strength refractory brick

    CN103693982A

  • Graphitized carbon fiber with high carbon element content and preparation method thereof

    CN113249826A

  • Aramid fiber reinforced high-performance concrete

    CN116589241A